Advances in the design and application of contactless conductivity detectors for separation, flow-through, microfluidic and sensing techniques: A review - Tůma, Petr (Analytica chimica acta, 2025)
The review focuses on the design of detection cells, the use of microcontrollers for processing and evaluation of the detection signal, and the development of multi-detection systems for electromigration, liquid chromatography, flow-through and microfluidic techniques. A separate section is the introduction of modern 3D printing techniques and the use of new printing materials for the design of multidetection systems. In addition to traditional utilisation in separation techniques, new versions of contactless conductivity detectors are finding applications in FIA, SIA, portable and paper based analytical systems or as independent sensors. Applicationwise, C4Ds find new use in gas detection, segmented flow monitoring, as part of point of care devices, and in many other biomedical, environmental, agricultural and industrial applications.
Keywords: Sensor; Contactless conductivity detection; Microfluidics; Capillary electrophoresis; Microcontroller; 3D printing